2013
DOI: 10.1111/all.12332
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory allergen from house dust mite is present in human milk and primes for allergic sensitization in a mouse model of asthma

Abstract: There is an urgent need to identify environmental risk and protective factors in early life for the prevention of allergy. Our study demonstrates the presence of respiratory allergen from house dust mite, Der p 1, in human breast milk. Der p 1 in milk is immunoreactive, present in similar amounts as dietary egg antigen, and can be found in breast milk from diverse regions of the world. In a mouse model of asthma, oral exposure to Der p through breast milk strongly promotes sensitization rather than protect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 17 publications
1
25
2
4
Order By: Relevance
“…Assuming that Ara h 6 represents 4% of peanut proteins, this would correspond to about 13 ng/ml of peanut proteins for 50 g of ingested peanut. Although this value is 15-fold lower than previously observed, that is, about 200 ng/ml (9), peak value of Ara h 6 (i.e., about 3 ng/ml) in our study corresponds to that observed for other allergens such as ovalbumin (8,38) or BLG (11,24,39). After milk ingestion, BLG was still detectable in 50% of milk samples collected 9-15 h after milk consumption (11), whereas few samples were still positive for peanut proteins after 8 h (9).…”
Section: A C B Dcontrasting
confidence: 70%
“…Assuming that Ara h 6 represents 4% of peanut proteins, this would correspond to about 13 ng/ml of peanut proteins for 50 g of ingested peanut. Although this value is 15-fold lower than previously observed, that is, about 200 ng/ml (9), peak value of Ara h 6 (i.e., about 3 ng/ml) in our study corresponds to that observed for other allergens such as ovalbumin (8,38) or BLG (11,24,39). After milk ingestion, BLG was still detectable in 50% of milk samples collected 9-15 h after milk consumption (11), whereas few samples were still positive for peanut proteins after 8 h (9).…”
Section: A C B Dcontrasting
confidence: 70%
“…A recent report has described that HDM is found in breast milk at a concentration similar to that in EW [19]. Sensitization to HDM via the intestine has been demonstrated using a murine model, and therefore sensitization via the ingestion of breast milk is possible.…”
Section: Discussionmentioning
confidence: 99%
“…We found that mice exposure to respiratory antigen resulted indeed in the presence of the antigen in breast milk [6,7,10], and more importantly, we could detect respiratory antigen, house dust mite (HDM) Dermatophagoides Pteronyssinus (Der p) 1, in human milk from various regions of the world [6]. Looking at literature in rodents can explain this observation.…”
Section: Evidence That Breastfeeding Can Affect Actively Immune Respomentioning
confidence: 64%
“…The presence of airborne antigens in milk most probably results from the transfer of antigen from the airways to the mammary gland, mainly through the gut and, for a small proportion, through the alveolar -capillary barrier of the lung. While we showed that OVA administration through breast milk resulted in prevention of allergic disease, either by Th1 differentiation in the case of soluble OVA [10] or by Foxp3 Tregs differentiation in the case of OVA in immune complexes [7], oral early exposure to HDM antigens through breast milk resulted in increased allergic sensitization in the progeny even though TGF-b and maternal antibodies were present in milk [6]. There are some important biological and functional differences between OVA and HDM antigens that could explain these observations.…”
Section: Evidence That Breastfeeding Can Affect Actively Immune Respomentioning
confidence: 77%